Synergistic Electrocatalysts for Alkaline Hydrogen Oxidation and Evolution Reactions - Tang, Tang; Ding, Liang; Yao, Ze‐Cheng; Pan, Hai‐Rui; Hu, Jin‐Song; Wan, Li‐Jun (Advanced functional materials, 2022)
Alkaline water electrolyzers (AWEs) and anion‐exchange membrane fuel cells (AEMFCs) have received increasing attention for their natural compatibility with earth‐abundant materials and are regarded as the cutting‐edge of hydrogen energy techniques and the research focuses. However, the commercialization of these devices remains in the sluggish hydrogen electrode reactions due to the requirement of cooperative adsorption of both hydrogen species and hydroxyl species. The research on synergistic alkaline hydrogen oxidation/evolution reaction (HOR/HER) electrocatalysts is still in its infancy. This review summarizes the recent progress and strategies in constructing synergistic active sites for advancing alkaline HOR/HER electrocatalysts. The fundamentals of alkaline HOR/HER are first introduced with both theoretical and experimental verifications to rationalizing the necessity of constructing synergistic active sites. Then, this review systemically dissects the functionality of different active sites in recently reported innovative HOR/HER catalysts and introduces the synergistic effects. Finally, some perspectives on the challenges and opportunities for the future design and synthesis of the synergistic HOR and HER electrocatalysts are proposed, intending to promote the application of hydrogen‐based energy conversion systems. In this review, the recent progress and strategies in constructing synergistic active sites for advancing alkaline hydrogen oxidation/evolution reaction electrocatalysts are systematically summarized, aiming at promoting the commercialization of hydrogen‐based energy conversion systems.